Going viral: A science communication collaboration in the era of COVID-19 and social media - Wiles, Siouxsie; Morris, Toby; Priestley, Rebecca (Frontiers in Communication, 2023)
On 9 March 2020, 2 days before the World Health Organization declared COVID-19 a global pandemic, two of the authors (microbiologist and infectious diseases expert Associate Professor Siouxsie Wiles and cartoonist Toby Morris) released their first output together: an animated GIF (Graphics Interchange Format) known as “Flatten the Curve”. The graphic went viral on Twitter with over 10 million impressions in 3 days. Flatten the Curve was the first of more than 70 graphics produced by our collaboration, all designed as accessible visual communication about COVID-19. The graphics, all released under a Creative Commons CC-BY-SA-4.0 license, have been translated into multiple languages, used by communities, politicians, and public health officials around the world, and the collaborators have won multiple awards for their work.